The Role of Internal Auditors in Preventing Fraud: A Literature Review - Abdul Rasak; Irensa Femmy; Gratia Triyana Nusa; Amiruddin Amiruddin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study explores the role of internal auditors in preventing and detecting fraud in public and private sector organizations, focusing on influencing factors and the evolution of their role in the digital era. Through a literature review of 37 articles from 2013–2025, the research identifies that internal auditors serve as guardians of organizational integrity by strengthening internal controls, early risk detection, and collaboration with external parties. Factors such as independence, experience, professional skepticism, and digital technology adoption are shown to enhance fraud prevention effectiveness. In the digital era, the internal auditor's role evolves with the integration of tools like CAATTs, AI, and whistleblowing systems, despite challenges like dependence on top management. These findings underscore the need for investment in digital competencies and strong governance to bolster internal auditors' roles in maintaining accountability and transparency.